2020
DOI: 10.1101/2020.03.29.014498
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cardio-centric hemodynamic management improves spinal cord oxygenation and mitigates hemorrhage in acute spinal cord injury

Abstract: 21Chronic high-thoracic and cervical spinal cord injury (SCI) results in a complex phenotype of 22 cardiovascular consequences, including impaired left-ventricular contractility. Here, we sought to 23 determine whether such dysfunction manifests immediately post-injury, and if so, whether 24 correcting impaired contractility can improve spinal cord oxygenation (SCO2), blood flow (SCBF) 25 and metabolism. Using a porcine model of SCI, we demonstrate that high-thoracic SCI acutely 26 impairs cardiac contracti… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Moreover, the use of some vasopressors might cause more complications in patients 49 while also potentially contributing to intra-spinal hemorrhage . In fact, recent results in acute experimental SCI suggest controlling for hemodynamic dysregulation through a cardiac-focused treatment instead of using standard vasopressors such as norepinephrine 50 .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the use of some vasopressors might cause more complications in patients 49 while also potentially contributing to intra-spinal hemorrhage . In fact, recent results in acute experimental SCI suggest controlling for hemodynamic dysregulation through a cardiac-focused treatment instead of using standard vasopressors such as norepinephrine 50 .…”
Section: Discussionmentioning
confidence: 99%
“…up to 4 h post‐injury), and level of injury (i.e. T2−3) are sufficient to cause a marked decrement in cardiac contractile function, evidenced by a significant reduction in E es in both rodent and porcine models (Fossey et al., 2022; Poormasjedi‐Meibod et al., 2019; Squair et al., 2018; Wainman et al., 2021; Williams et al., 2020). Moreover, in a recent manuscript, describing a series of experiments in both rodents and individuals with SCI, we reported that SCI induces considerable contractile dysfunction post‐injury that occurs due to the loss of bulbospinal sympathetic control over the heart (Fossey et al., 2022).…”
Section: Methodsmentioning
confidence: 99%
“…Second, cervical spinal cord injury also damages the supraspinal vasomotor pathway innervating the sympathetic preganglionic neurons (1,27). Therefore, sympathetic activity might be reduced, causing hypotension and hypoperfusion of the spinal cord (34,35,42). The impaired systemic and central hemodynamics attenuate the oxygen supply to the spinal cord.…”
Section: Impact Of Cervical Spinal Cord Contusion On Spinal Cord Oxyg...mentioning
confidence: 99%
“…Cervical spinal cord injuries usually cause cardiorespiratory dysfunctions and result in systemic and central hypoxia due to damage to supraspinal respiratory and vasomotor pathways (10,18,19,24,27,38,41,43). In addition, the cervical spinal cord has more extensive microvascular structures than other spinal cord segments (39).…”
Section: Introductionmentioning
confidence: 99%